5a+2 =2 (4+a)
Simplifying
5a + 2 = 2(4 + a)
Reorder the terms:
2 + 5a = 2(4 + a)
2 + 5a = (4 * 2 + a * 2)
2 + 5a = (8 + 2a)
Solving
2 + 5a = 8 + 2a
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-2a' to each side of the equation.
2 + 5a + -2a = 8 + 2a + -2a
Combine like terms: 5a + -2a = 3a
2 + 3a = 8 + 2a + -2a
Combine like terms: 2a + -2a = 0
2 + 3a = 8 + 0
2 + 3a = 8
Add '-2' to each side of the equation.
2 + -2 + 3a = 8 + -2
Combine like terms: 2 + -2 = 0
0 + 3a = 8 + -2
3a = 8 + -2
Combine like terms: 8 + -2 = 6
3a = 6
Divide each side by '3'.
a = 2
Simplifying
a = 2